2011
DOI: 10.1007/s10551-011-0891-0
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Affect of Workplace Spirituality on the Relationship of Job Overload and Job Satisfaction

Abstract: With the increase in market competition and dynamic work environment, work overload seems to have become a common issue suffered by almost every employee. Overload usually results in not only poor health conditions but also mental circumstances. These problems then become a threat to the organizations in the form of poor performance and lack of ability to reach standards. Workplace spirituality is one way to deal with stressful overload conditions. This research deals with the study of moderating affects of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
167
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(200 citation statements)
references
References 13 publications
(12 reference statements)
14
167
0
10
Order By: Relevance
“…An earlier study conducted by Milliman et al (2003) among part-time employees revealed significant positive relationships between certain dimensions of spirituality and job satisfaction. Later, other studies have also shown that in organizations where spirituality is respected, employees experience greater job satisfaction (Pawar, 2009;Chawla & Guda, 2010;Altaf & Awan, 2011;Lazar, 2010). Hence, employees whose spiritual needs are fulfilled tend to be more satisfied with their jobs.…”
Section: Relationship Between Workplace Spirituality and Job Satisfacmentioning
confidence: 93%
“…An earlier study conducted by Milliman et al (2003) among part-time employees revealed significant positive relationships between certain dimensions of spirituality and job satisfaction. Later, other studies have also shown that in organizations where spirituality is respected, employees experience greater job satisfaction (Pawar, 2009;Chawla & Guda, 2010;Altaf & Awan, 2011;Lazar, 2010). Hence, employees whose spiritual needs are fulfilled tend to be more satisfied with their jobs.…”
Section: Relationship Between Workplace Spirituality and Job Satisfacmentioning
confidence: 93%
“…powołania, motywowane dodatkowo czynnikami religijno-duchowymi, przejawiają dużą determinację w wyborze i realizacji zawodu oraz odczuwają nie tylko większą satysfakcję z wykonywanej pracy, lecz także odznaczają się podwyższonym poziomem zadowolenia z obranego kierunku studiów i ścieżki zawodowej (por. Koenig i współpracownicy, 2001;Dik, Sargent i Steger, 2008;Paloutzian i współpra-cownicy, 2010;Duffy, Reid i Dik, 2010;Altaf, Awan, 2011;Park, 2012;Dik, Duffy i Tix, 2012). I tak Miller-Perrin i Thompson (2005;por.…”
Section: Duchowość I Religijność a Kariera Zawodowaunclassified
“…In an increasingly competitive environment, work overload is not an uncommon issue faced by most of the employees. It is considered to be a real problem in almost every organization (Altaf and Awan, 2011). The cause of stress happens to be the work overload resulting from time constraint and complexity of work (Mazloum et al, 2008).…”
Section: Job Stress and Turnover Intentionsmentioning
confidence: 99%